2004
DOI: 10.1002/nbm.869
|View full text |Cite
|
Sign up to set email alerts
|

Preinvasive and invasive cervical cancer: an ex vivo proton magic angle spinning magnetic resonance spectroscopy study

Abstract: The aim of this study was to obtain (1)H MR spectra using magic angle spinning (MAS) techniques from punch biopsies (<20 mg) of preinvasive and invasive cervical disease and to correlate the spectral profiles with sample classification on the basis of histopathology. Tissue samples were obtained at colposcopic examination, during local treatment of cervical intraepithelial neoplasia (CIN) or at hysterectomy. (1)H MAS MRS was performed at 25 degrees C while spinning the sample at 4.5 kHz. After measurement, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 28 publications
6
53
0
Order By: Relevance
“…In particular, it proved to be very powerful for corroborating and complementing noninvasive in vivo magnetic resonance spectroscopy studies by aiding assignment and quantification of the in vivo data, generally characterised by poor resolution and signal-tonoise at clinical magnetic field strengths [10][11][12][13][14]. Moreover, much research work has focused on the metabolic differentiation between tumour and healthy tissues, aiming to find possible biomarkers for the presence and/or grade of different cancers such as breast [15,16], brain [17,18], prostate [19][20][21], cervical [22][23][24], colorectal [25,26], hepatic [27], renal [28,29] and gastric cancer [30].…”
Section: Introductionmentioning
confidence: 97%
“…In particular, it proved to be very powerful for corroborating and complementing noninvasive in vivo magnetic resonance spectroscopy studies by aiding assignment and quantification of the in vivo data, generally characterised by poor resolution and signal-tonoise at clinical magnetic field strengths [10][11][12][13][14]. Moreover, much research work has focused on the metabolic differentiation between tumour and healthy tissues, aiming to find possible biomarkers for the presence and/or grade of different cancers such as breast [15,16], brain [17,18], prostate [19][20][21], cervical [22][23][24], colorectal [25,26], hepatic [27], renal [28,29] and gastric cancer [30].…”
Section: Introductionmentioning
confidence: 97%
“…MLR have been shown to be involved in tumour cell physiology, growth and metastasis (5) and cellular studies, which measure various lipid components in defined conditions, have demonstrated a correlation between an increase in MLR with suppressed proliferation (6)(7)(8), ongoing apoptosis (9)(10)(11)(12), growth arrest (7,12), and necrosis (13,14). In tissue studies, metabolic profiling of cervical biopsies (15)(16)(17) and other cancers (18,19) with magnetic resonance spectroscopy has been previously described, but measurement of MLR peaks has been confounded by signals from low molecular weight metabolites which complicate peak assignment and quantification. Several methods have been used to improve the discrimination of lipid signals from those of low molecular weight metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In this regard, proton MAS NMR combined with T 2 -filtering has been used to narrow the resonances from small molecules and improve the resolution of intact cells and tissues spectra, allowing weak resonances associated with metabolites present at low concentrations to be revealed. [11][12][13][14][15] The nondestructive nature of the technique allows the acquisition of metabolic information directly from cells with minimal preparation and their analysis by other methods. In addition, the solid state approach offers the advantage over conventional liquid state NMR (i.e., used in analysis of cells extracts) of simultaneous observation of lipophilic and hydrophilic metabolites.…”
Section: Introductionmentioning
confidence: 99%